Injection‐induced seismicity on basement faults including poroelastic stressing. Issue 4 (20th April 2016) - Chang, K. W.; Segall, P.
Abstract: Most significant induced earthquakes occur on faults within the basement beneath sedimentary cover. In this two‐dimensional plane strain numerical study, we examine the full poroelastic response of basement faults to fluid injection into overlying strata, considering both (1) the permeability of the fault zone and (2) the hydraulic connectivity of the faults to the target horizon. Given hydraulic and mechanical properties, we compute the spatiotemporal change in Coulomb stress, which we separate into (1) the change in poroelastic stresses Δ τ s + f Δ σ n, where Δ τ s and Δ σ n are changes in shear and normal stress (Δ τ s >0 and Δ σ n >0 both favor slip), and (2) the change in pore pressure f Δ p . Pore pressure diffusion into hydraulically connected, permeable faults dominates their mechanical stability. For hydraulically isolated or low‐permeability faults, however, poroelastic stresses transmitted to deeper basement levels can trigger slip, even without elevated pore pressure. The seismicity rate on basement fault zones is predicted using the model of Dieterich (1994). High seismicity rates can occur on permeable, hydraulically connected faults due to direct pore pressure diffusion. Lower rates are predicted on isolated steeply dipping normal faults, caused solely by poroelastic stressing. In contrast, seismicity on similarly oriented reverse faults is inhibited. Key Points: We model injection into reservoir above basement faults including full poroelastic coupling Pore pressure diffusion increases seismicity rates on hydraulically connected and conductive faults Indirect poroelastic stressing may induce seismicity on hydraulically isolated faults